Dampak Pembelajaran Jarak Jauh Terhadap Psikologis Anak - Hanny nur alifia; Kuswanto Kuswanto; Prihantini Prihantini (Universitas Negeri Makassar, 2021)
This study was created to provide information about the impact of distance learning during the Covid-19 pandemic on children's psychology. The method used is a qualitative method with a descriptive study approach. The existence of the Covid-19 outbreak has made learning done remotely. This is certainly a learning style that is still very common among children in Indonesia, very foreign to them and something new to children in Indonesia. To improve the quality of learning that has been done during this pandemic, we must know the impact that children are receiving or feeling during this distance learning. Is it good or bad for child psychology. And to see what can affect other than psychological. As well as what needs to be considered during distance learning so that it is effective and in accordance with what students need, what needs to be improved from the distance learning that has occurred. This distance learning certainly has its positives and negatives which are used as evaluation materials for educators, especially teachers. In order to be able to change the negative impact into a positive thing. Because this psychological aspect is important to discuss especially in the current pandemic era, which of course really needs more attention to distance learning that children go through.